SIRT6’s function in controlling the metabolism of lipids and glucose in diabetic nephropathy - Wang, Ying; Liu, Tongtong; Cai, Yuzi; Liu, Weijing; Guo, Jing (Frontiers in Endocrinology, 2023)
Diabetic nephropathy (DN) is a complication of diabetes mellitus (DM) and the main cause of excess mortality in patients with type 2 DM. The pathogenesis and progression of DN are closely associated with disorders of glucose and lipid metabolism. As a member of the sirtuin family, SIRT6 has deacetylation, defatty-acylation, and adenosine diphosphate-ribosylation enzyme activities as well as anti-aging and anticancer activities. SIRT6 plays an important role in glucose and lipid metabolism and signaling, especially in DN. SIRT6 improves glucose and lipid metabolism by controlling glycolysis and gluconeogenesis, affecting insulin secretion and transmission and regulating lipid decomposition, transport, and synthesis. Targeting SIRT6 may provide a new therapeutic strategy for DN by improving glucose and lipid metabolism. This review elaborates on the important role of SIRT6 in glucose and lipid metabolism, discusses the potential of SIRT6 as a therapeutic target to improve glucose and lipid metabolism and alleviate DN occurrence and progression of DN, and describes the prospects for future research.